The concept of the epithet and its argument according to the fundamentalists and its examples in the Quran and Sunnah - Al-Qudah, Nader Mohammed; Rababaa, Basma Ali (Journal of Islamic Sciences, 2020)
The study aimed to define the concept of the epithet of the fundamentalists and explain its validity, and knowledge of its governance, and how to use the concept of the epithet to reach an understanding of the word of the book and the year, and some of the methods of scientists to understand the science of semantics.To achieve the objective of the study, the researcher followed the analytical fundamentalist approach, which is based on studying the issue, extrapolating the legal texts related to it, analyzing it and devising the legal rulings.The study showed that the concept of the epithet is one of the weakest concepts and that it is not considered an argument among the fundamentalists and has been taken only by the few oligarchs. The researcher responded to the statements and discussed them to both parties and then drew the most correct view based on the closest to the book and the Sunna.The researcher who is interested in the fundamentals of jurisprudence and scholars especially recommends the need to study these concepts more extensively in order to understand the semantics that leads to understanding the text and derive the legal rulings from them and the students' need for such a study so that they know and understand the meaning of the word.
Keywords: Usul al- Figh; Authentic Title; The Concept of Violation